2016
DOI: 10.1093/her/cyv101
|View full text |Cite
|
Sign up to set email alerts
|

School district wellness policy quality and weight-related outcomes among high school students in Minnesota

Abstract: Weight-related outcomes were examined among high school students in Minnesota public school districts according to the quality of district wellness policies. Wellness policy strength and comprehensiveness were scored using the Wellness School Assessment Tool (WellSAT) for 325 Minnesota public school districts in 2013. The associations between WellSAT scores and district-level means of high school student responses to a statewide survey of health behaviors were examined in this ecologic study. WellSAT Total Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Distributing and providing model policies, although important, may not be enough. An assessment of nearly 300 district wellness policies in Minnesota revealed that 29% of districts adopted the exact language of template policies developed by statewide associations . Template policies generally have significantly weaker language and are less comprehensive than tailored wellness policies .…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Distributing and providing model policies, although important, may not be enough. An assessment of nearly 300 district wellness policies in Minnesota revealed that 29% of districts adopted the exact language of template policies developed by statewide associations . Template policies generally have significantly weaker language and are less comprehensive than tailored wellness policies .…”
Section: Discussionmentioning
confidence: 95%
“…Template policies generally have significantly weaker language and are less comprehensive than tailored wellness policies . This research emphasizes the importance of specific and comprehensive wellness policies to achieve desired student outcomes …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations